DIURETIC ACTIVITY TEST OF RED BETEL LEAF ETHANOL EXTRACT (PIPER CROCATUM RUIZ & PAV) AGAINST MALE WHITE RATS (RATTUS NOVERGICUS) - Rizka Hasmi Nasution; Jefri Naldi; Sri Handayani; Efrita Lestari (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Abstract: Background: According to the World Health Organization (WHO), the prevalence of hypertension in the world reached over 1.13 billion people in 2015, implying that one out of every three persons was diagnosed with hypertension. Flavonoids found in red betel leaves (Piper crocatum Ruiz & Pav) serve as antifungals, diuretics, antihistamines, antihypertensives, insecticides, bactericidal, antiviral, and enzyme inhibitors. The study aimed to find the best dose of red betel leaves extract as a diuretic in male white rats.The study was experimental laboratory. Alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids are among the phytochemicals tested. A total of 25 male white rats were separated into five groups. Red betel leaves extract was administered to groups 1, 2, and 3 at dosages of 250mg/kg, 350 mg/kg, and 650mg/kg, respectively. Group 4 received a 0.5% Na CMC suspension as a negative control, while Group 5 received a furosemide suspension as a positive control. The average urine volume at 1-6 hours and the buildup of urine were used to calculate the rat urine volume.The results showed the accumulation of urine volume for 6 hours. The treatment group of red betel leaf ethanol extract at a dose of 250mg/kgBW obtained 0.57mL, a dose of 350mg/kgBW obtained 2.38mL, and a dose of 650mg/kgBW obtained 4.29mL, negative control (CMC 0.5%) obtained 0.2mL, positive control obtained 27.52mL.The study concluded that red betel leaves extract has diuretic action and that the ethanol extract of red betel leaves at a dosage of 650 mg/kgBW is the most effective dose.